101k views
5 votes
Rewrite the function f(x)=3(x-1)^2+9 in the form f(x)=ax^2+bx+c

1 Answer

3 votes

Answer:

f(x) = 3x² - 6x + 12

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Expand by FOIL (First Outside Inside Last)
  • Standard Form: f(x) = ax² + bx + c
  • Vertex Form: f(x) = a(bx + c)² + d

Explanation:

Step 1: Define function

Vertex Form: f(x) = 3(x - 1)² + 9

Step 2: Find Standard Form

  1. Expand by FOILing: f(x) = 3(x² - 2x + 1) + 9
  2. Distribute 3: f(x) = 3x² - 6x + 3 + 9
  3. Combine like terms (constants): f(x) = 3x² - 6x + 12
User Matteodv
by
5.0k points